FLASH FICTION STORY, AN AUTHENTIC TEXT FOR LITERACY DEVELOPMENT IN SPANISH AS A FOREIGN LANGUAGE - Babina, Agata (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
The present study is based on flash fiction texts as a tool for literacy. Literacy has been highlighted as one of the main ideas in the new Educational Standard of Latvia (in force since September 2020). This fact, followed by Solvita Berra’s recent research on original texts in foreign language teaching, leads to the exploration of flash fiction stories (sp. microrrelatos) as an authentic text and a perfect tool for promoting literacy in the Spanish as a foreign language (ELE) classroom, since it blends perfectly with a variety of creative writing exercises. The flash fiction is a narrative genre that has had a great impact on the Spanish academic field in recent decades. The introduction of flash fiction in the ELE classroom has so far been proposed in several master’s dissertations, but its research at a scientific level is still very scarce. The benefits of the introduction of this literary genre in didactics have been treated at the doctoral thesis level by Belén Mateos Blanco (University of Valladolid) and later published in the manual "The flash fiction as a didactic tool in the teaching of ELE", and few others. However, flash fiction stories are good socio-cultural references and serve both, for the teaching of different literary, linguistic and sociocultural aspects, as well as for the promotion of literacy. In addition, they represent a great variety of Spanish, since they have been written by authors from almost all Spanish-speaking countries. The empirical part of the article presents two didactic Units developed based on the use of flash fiction stories for the A1–A2 and B1 Spanish acquisition level. These two units form part of a 20-unit didactic material created as a result of a doctoral thesis. Here published proposal has been proved in the classwork with University of Liepaja students of the 1st and 2nd year of Spanish studies.